Thermal Modeling of Thin Lubricant Film Within Piston Compression Ring and Rough Cyliner Liner Conjuction - Mishra, Prakash Chandra (Frontiers in Mechanical Engineering, 2020)
This work is devoted to develop a transient thermo elastohydrodynamic model for thermal analysis of micro scale oil film with in piston compression ring-liner conjunction. In this paper, heat dissipation through piston to cylinder wall mainly considered via thin film of lubricant on convection and conduction mode. It also includes frictional heat generated due to ring liner co-action while balancing total heat of the engine system. Results presented in this paper show that frictional heating raises additional lubricant temperature of 900 C. Such increase in temperature is one of the reasons for presence of further oil degradation in high pressure zone of engine cycle, which appears between 3000 to 4000 crank location.